Foundations of Social Work - Kučinskas, Vytolis (Acta Paedagogica Vilnensia, 2000)
Ideological, political, sociological, psychological, pedagogical and medical foundations of social work are presented in the article. The information is necessary for the training of social workers and especially – preparing social pedagogues and teachers.